Characterisation of multicrystalline solar cells - A.Q. Malik; Chong Chew Hah; Chan Siang Khwang; Lim Chee Ming; Tan Kha Sheng (ASEAN Journal on Science and Technology for Development, 2006)
The evaluation and assessment of the performance of photovoltaic (PV) cells in terms of measurable parameters requires the measurement of the current as a function of voltage, temperature, intensity, wind speed and spectrum. Mo st noticeable of all these parameters is the PV conversion efficiency ?, defined as the maximum electrical power Pmax produced by the PV cell divided by the incident photon power P in which is measured with respect to standard test conditions (STC). These conditions refer to the spectrum (AM 1.5), solar radiation intensity (1000 Wm-2), cell temperature (25 ±2oC) and wind speed (2 mph). Tests under STC are carried out in the laboratory at a controlled environment. There have been several studies that analyze uncertainties in the laboratory measurement of solar cell efficiencies using different solar simulators and their transference to operational situations. Our preliminary results demonstratethat the short circuit current (ISC) of the solar cell decreases when irradiance is less than 1000 Wm-2 irrespective of the working temperature of the cell.